Anti-static and radiation-proof concrete
By using specific ratio strontium ferrite and hafnium boride additives in concrete, the problem of static charge accumulation in radiation-proof concrete is solved, and excellent anti-static and radiation-proof performance is achieved, reducing the static potential and electromagnetic radiation hazards. , improves the durability and safety of concrete.
Patent Information
- Application Number
- CN202410249734.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-03-05
AI Technical Summary
Existing radiation-proof concrete is prone to accumulation of static charge during preparation and use, leading to fire, explosion, electric shock and signal interference, and affects electronic equipment and control systems, and may cause corrosion and damage in high humidity environments.
Using strontium ferrite and hafnium boride with specific ratios as additives, through their conductive properties and magnetic properties, the electrostatic potential of the concrete surface is reduced, and the electromagnetic wave energy is absorbed and scattered, forming stable physical and chemical bonding, and improving the durability of concrete. and safety, and improve its microstructure and density to enhance antistatic properties.
The excellent anti-static and radiation-proof properties of concrete are achieved, the electrostatic potential is reduced, the harm of electromagnetic radiation is reduced, the durability and safety are improved, and the radiation-proof and mechanical properties are enhanced.
Smart Images

Figure BDA0004727183040000041 
Figure BDA0004727183040000051 
Figure BDA0004727183040000052
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to an anti-static and anti-radiation concrete. Background Art
[0002] Radiation-proof concrete, also known as shielding concrete or ray-proof concrete, has a large specific gravity and is able to shield gamma rays, X-rays or neutron radiation, and is not easily penetrated by radiation. The cementitious material in radiation-proof concrete generally uses silicate cement with low hydration heat, or special cements such as high-alumina cement, barium cement, and magnesia cement; uses barite, magnetite, limonite, and scrap iron as aggregates; and adds substances containing boron, cadmium, and lithium to reduce the penetration strength of neutron flux.
[0003] Radiation-proof concrete is often used as a substitute for expensive radiation-proof materials such as lead and steel. It can shield X-rays, gamma rays and neutron radiation, and is used for the protection of atomic reactors, particle accelerators, and radioactive isotope equipment in industry, agriculture and scientific research departments.
[0004] In the current radiation-proof concrete, barite is mostly used as the radiation-proof aggregate. The specific gravity of barite is 4300kg / m 3 -4700kg / m 3 It is mainly produced in Shaanxi, Hubei, Shandong and other places. Because the material is relatively brittle, the raw materials obtained from various places are angular and needle-like, which is not conducive to pumping.
[0005] At the same time, static charges may accumulate in the process of preparation and use of concrete due to various reasons. The accumulation of static charges may lead to the following problems: risk of fire or explosion. Static charges may generate sparks or arcs in some cases, which may ignite flammable materials or cause explosions; risk of electric shock. If workers come into contact with concrete structures with static charges, they may suffer electric shocks due to static charge discharge; signal interference. For some electronic equipment or control systems, the accumulation of static charges may interfere with their signal transmission, thereby affecting the normal operation of the equipment; and corrosion and damage. The accumulation of static charges may also cause corrosion and damage to materials, especially in some high-humidity environments, where such corrosion and damage will be more obvious.
[0006] Therefore, there is an urgent need to provide a kind of concrete with excellent antistatic and radiation protection performance. Summary of the invention
[0007] In order to solve at least one of the above technical problems, a concrete with excellent anti-static and anti-radiation properties is developed. The present application provides an anti-static and anti-radiation concrete.
[0008] An antistatic and radiation proof concrete comprises the following raw materials in parts by weight: 250-380 parts of cement, 70-200 parts of steel slag, 500-750 parts of river sand, 600-800 parts of crushed stone, 125-190 parts of water and 35-65 parts of additives;
[0009] Wherein, the additive is one or two of strontium ferrite and hafnium boride.
[0010] By adopting the above technical solution, the concrete prepared by the specific proportion and specific components in the present application has excellent anti-static and anti-radiation properties.
[0011] Strontium ferrite has excellent electrical conductivity, can effectively transfer and release static charges, reduce the electrostatic potential of the concrete surface, and effectively absorb and scatter electromagnetic wave energy. It can also modulate electromagnetic waves through its magnetic properties and convert them into heat energy or other forms of energy, thereby reducing the hazards of electromagnetic radiation. At the same time, strontium ferrite can also interact with other components in concrete to form more stable physical and chemical bonds, thereby improving the durability and safety of concrete.
[0012] Hafnium boride has tiny conductive channels that can effectively transfer and release static charges, thereby reducing the electrostatic potential of the concrete surface, and further enhance its antistatic properties by improving the microstructure of concrete and increasing its density. It can reduce microcracks and micropores inside the concrete, thereby reducing the possibility of static charge accumulation on the concrete surface. At the same time, hafnium boride has excellent high-temperature mechanical properties and antioxidant properties, and can maintain its stability under high temperature, high pressure and extreme environments, as well as improve the radiation resistance and mechanical properties of concrete.
[0013] Optionally, the weight proportion of the additive is 42-55 parts.
[0014] Preferably, the weight portion of the additive is 50 parts.
[0015] By adopting the above technical solution, the present application uses a better proportion of additives, and the comprehensive performance of the prepared concrete is more excellent.
[0016] Optionally, the ratio of the weight of the additive to the sum of the weight of the cement and the steel slag is 0.07-0.144:1.
[0017] Optionally, the additives are strontium ferrite and hafnium boride.
[0018] Optionally, the weight ratio of the strontium ferrite to the hafnium boride is 1-1.5:1.
[0019] Preferably, the weight ratio of the strontium ferrite to the hafnium boride is 1:1, 1.2:1 and 1.5:1.
[0020] By adopting the above technical solution, the present application adopts a composite system of strontium ferrite and hafnium boride in a specific ratio, and the comprehensive performance of the prepared concrete is more excellent, which can effectively improve the radiation protection performance of the concrete.
[0021] Optionally, strontium ferrite is replaced with modified strontium ferrite, and the raw materials of the modified strontium ferrite include a surface treatment agent, a polyurethane emulsion and strontium ferrite, and the weight ratio of the surface treatment agent, the polyurethane emulsion and the strontium ferrite is 4:100:30.
[0022] Optionally, the surface treatment agent is obtained by mixing sodium hexametaphosphate, sodium dodecyl sulfate and ethanol solution in a weight ratio of 3:1:100.
[0023] Wherein, the preparation method of modified strontium ferrite is:
[0024] 1) mixing sodium hexametaphosphate, sodium lauryl sulfate and ethanol solution to obtain a surface treatment agent;
[0025] 2) adding the surface treatment agent prepared in step 1) into the polyurethane solution and mixing and stirring to obtain a modified polyurethane solution;
[0026] 3) Putting the strontium ferrite into the modified polyurethane emulsion prepared in step 2) for ultrasonic treatment and drying to obtain strontium ferrite I, and putting the dried strontium ferrite I into the modified polyurethane emulsion for ultrasonic and drying treatments, repeating the process several times to obtain modified strontium ferrite.
[0027] Preferably, the weight ratio of sodium hexametaphosphate, sodium lauryl sulfate and ethanol solution in step 1) is 3:1:100;
[0028] Preferably, the repetition multiple times in step 3) refers to repetition 2, 3, 4, 5 or 6 times;
[0029] Preferably, the frequency of the ultrasonic treatment in step 3) is 30 kHz, and the ultrasonic treatment time is 15 min.
[0030] Specifically, the preparation method of modified strontium ferrite is as follows: sodium hexametaphosphate, sodium dodecyl sulfate and ethanol solution in a weight ratio of 3:1:100 are mixed to obtain a surface treatment agent, the surface treatment agent is put into a polyurethane solution and mixed and stirred to obtain a modified polyurethane solution, strontium ferrite is put into a modified polyurethane emulsion for ultrasonic treatment and then dried to obtain strontium ferrite I, and the dried strontium ferrite I is further put into the modified polyurethane emulsion for ultrasonic and drying treatment, and this step is repeated 6 times to obtain modified strontium ferrite, wherein the frequency of the ultrasonic treatment is 30kHz, and the ultrasonic treatment time is 15min; the weight ratio of the surface treatment agent, the polyurethane emulsion and the strontium ferrite is 4:100:30.
[0031] By adopting the above-mentioned technical scheme, the strontium ferrite used in the present application is wrapped and modified with a polyurethane emulsion, which effectively improves the dispersibility and compatibility of the strontium ferrite, so that the strontium ferrite is more evenly distributed in the concrete, forming a more stable structure, further improving the anti-static and anti-radiation properties of the concrete, and avoiding the agglomeration of the strontium ferrite due to its own magnetism, thereby affecting the overall anti-radiation performance.
[0032] Optionally, the average particle size of the steel slag is 1-5 mm.
[0033] Optionally, the fineness modulus of the river sand is 2.3-2.9.
[0034] Optionally, the average particle size of the crushed stone is 6-15 mm.
[0035] In summary, the present invention includes at least one of the following beneficial technical effects:
[0036] 1. The concrete prepared by the specific proportion and specific components in this application has excellent anti-static and anti-radiation properties;
[0037] 2. Strontium ferrite has excellent electrical conductivity, which can effectively transfer and release static charges and reduce the electrostatic potential of the concrete surface; it can also effectively absorb and scatter electromagnetic wave energy, and can also modulate electromagnetic waves through its magnetic properties to convert them into heat energy or other forms of energy, thereby reducing the harm of electromagnetic radiation; at the same time, strontium ferrite can also interact with other components in concrete to form more stable physical and chemical bonds, thereby improving the durability and safety of concrete;
[0038] 3. Hafnium boride can effectively transfer and release static charges, thereby reducing the electrostatic potential on the concrete surface, and further enhance its anti-static properties by improving the microstructure of concrete and increasing its density. It can reduce microcracks and micropores inside the concrete, thereby reducing the possibility of static charge accumulation on the concrete surface, and improve the radiation resistance of concrete. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to the embodiments.
[0040] The present application designs an anti-static and anti-radiation concrete, which includes the following raw materials in parts by weight: 250-380 parts of cement, 70-200 parts of steel slag, 500-750 parts of river sand, 600-800 parts of crushed stone, 125-190 parts of water and 35-65 parts of additives;
[0041] Wherein, the additive is one or two of strontium ferrite and hafnium boride.
[0042] A method for preparing antistatic and radiation-proof concrete comprises the following steps: adding cement, steel slag, river sand, crushed stone, water and additives in sequence, mixing and stirring, and preparing the antistatic and radiation-proof concrete. Specific embodiments
[0044] The raw material models of this application are as follows. Unless otherwise specified, the raw materials of this application are all commercially available:
[0045] Cement: selected from 42.5 grade ordinary Portland cement;
[0046] Steel slag: chemical composition includes calcium oxide 40-60%, silicon dioxide 4-10%, aluminum oxide 2-8%, iron oxide 2-8%;
[0047] Water: selected from tap water;
[0048] Strontium ferrite: Hubei Xinkang Pharmaceutical Chemical Co., Ltd.;
[0049] Barium ferrite: Hubei Guangao Biotechnology Co., Ltd.;
[0050] Hafnium boride: Brand, Shishun;
[0051] Sodium hexametaphosphate: purity 99%;
[0052] Sodium dodecyl sulfate: Xi'an Taihua Pharmaceutical Technology Co., Ltd.;
[0053] Ethanol solution: concentration is 95%;
[0054] Polyurethane emulsion: solid content is 65%.
[0055] Test items and methods:
[0056] Radiation protection performance test: refer to the method of "GB 18871-2002 Basic Standard for Ionizing Radiation Protection and Radiation Source Safety";
[0057] Surface resistivity (Ω): Refer to GB / T 1410-2006 Test method for volume resistivity and surface resistivity of solid insulating materials.
[0058] Examples 1-3
[0059] The specific raw material weights of an anti-static and radiation-proof concrete of Example 1-3 are shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] Among them, the additive is strontium ferrite; the average particle size of steel slag is 5mm; the fineness modulus of river sand is 2.3; the average particle size of crushed stone is 6mm; the cement is 42.5 grade ordinary Portland cement; the chemical composition of steel slag includes 40-60% calcium oxide, 4-10% silicon dioxide, 2-8% aluminum oxide, and 2-8% iron oxide.
[0064] Embodiment 4-7
[0065] Based on Example 2, except for the weight of the additives, the other components and preparation methods are the same as those of Example 2.
[0066] Example 4
[0067] The weight of the additive is 42 kg.
[0068] Example 5
[0069] The weight of the additive is 50 kg.
[0070] Example 6
[0071] The weight of the additive was 55 kg.
[0072] Example 7
[0073] The weight of the additive is 65 kg.
[0074] Comparative Example 1
[0075] Based on Example 2, except that no additives are added, the other components and preparation methods are the same as those of Example 2.
[0076] Comparative Example 2
[0077] Based on Example 2, except that an equal amount of barium ferrite is used to replace strontium ferrite, the other components and preparation methods are consistent with those of Example 2.
[0078] The concrete prepared in Examples 1-7 and Comparative Examples 1-2 was subjected to performance testing, and the test results are shown in Table 2.
[0079] Table 2
[0080]
[0081]
[0082] It can be seen from Examples 1-3, Comparative Examples 1-2 and Table 2 that the concrete prepared by the specific components of the present application has excellent anti-static and anti-radiation properties. According to the radiation protection performance test, the linear attenuation coefficient of gamma rays and neutron rays is high, and the surface resistivity is low;
[0083] As can be seen from Examples 2, 4-7 and Table 2, the use of a more optimal weight of additives in the present application is more conducive to improving the radiation protection performance of concrete and reducing the surface resistivity;
[0084] It can be seen from Comparative Examples 1-2, Example 2 and Table 2 that the present application uses additives, and when the additive is strontium ferrite, it has excellent conductive properties, can effectively transfer and release static charges, reduce the electrostatic potential on the concrete surface, and effectively absorb and scatter electromagnetic wave energy, thereby improving the antistatic and radiation protection properties of the prepared concrete.
[0085] Embodiment 8-11
[0086] Based on Example 5, except for the different types of additives, the total weight of the additives remains unchanged, and the other components and preparation methods are consistent with Example 5.
[0087] Example 8
[0088] The additive is hafnium boride.
[0089] Example 9
[0090] The additive is composed of a mixture of strontium ferrite and hafnium boride in a weight ratio of 1:1.
[0091] Example 10
[0092] The additive is composed of a mixture of strontium ferrite and hafnium boride in a weight ratio of 1.2:1.
[0093] Embodiment 11
[0094] The additive is composed of a mixture of strontium ferrite and hafnium boride in a weight ratio of 1.5:1.
[0095] Example 12
[0096] Based on Example 10, except that the strontium ferrite is replaced by modified strontium ferrite, the other components and preparation methods are the same as those of Example 10;
[0097] The preparation method of modified strontium ferrite is as follows: sodium hexametaphosphate, sodium dodecyl sulfate and ethanol solution in a weight ratio of 3:1:100 are mixed to obtain a surface treatment agent, the surface treatment agent is put into a polyurethane solution and mixed and stirred to obtain a modified polyurethane solution, strontium ferrite is put into a modified polyurethane emulsion for ultrasonic treatment and then dried to obtain strontium ferrite I, and the dried strontium ferrite I is further put into the modified polyurethane emulsion for ultrasonic and drying treatment, and this step is repeated 6 times to obtain modified strontium ferrite, wherein the frequency of the ultrasonic treatment is 30kHz and the ultrasonic treatment time is 15min; the weight ratio of the surface treatment agent, the polyurethane emulsion and the strontium ferrite is 4:100:30.
[0098] Examples 13-14
[0099] Based on Example 12, except for the different properties of steel slag, river sand and gravel, the other components and preparation methods are consistent with Example 12.
[0100] Embodiment 13
[0101] The average particle size of steel slag is 3 mm;
[0102] The fineness modulus of river sand is 2.6;
[0103] The average particle size of the crushed stone is 10 mm.
[0104] Embodiment 14
[0105] The average particle size of steel slag is 1 mm;
[0106] The fineness modulus of river sand is 2.9;
[0107] The average particle size of the crushed stone is 15 mm.
[0108] The concrete prepared in Examples 13-14 was subjected to performance testing, and the test results are shown in Table 3.
[0109] Table 3
[0110]
[0111] It can be seen from Examples 8-11 that the additive of the present application uses a specific ratio of strontium ferrite and hafnium boride to effectively improve the comprehensive performance of concrete; wherein, the hafnium boride used in the present application has a tiny conductive channel, which can effectively transfer and release static charge, thereby reducing the electrostatic potential on the surface of the concrete, and further enhance its antistatic performance by improving the microstructure of the concrete and increasing its density, which can reduce the microcracks and micropores inside the concrete, thereby reducing the possibility of static charge accumulation on the surface of the concrete, and improve the radiation resistance of the concrete; at the same time, it can be well dispersed in the concrete, thereby improving the antistatic and radiation protection properties of the concrete, and can better fill the pores and microcracks of the concrete to form a uniform conductive and radiation absorption network, thereby improving the overall performance of the concrete;
[0112] It can be seen from Example 12 and Table 3 that the strontium ferrite used in the present application is modified by encapsulating with a polyurethane emulsion, which effectively improves the dispersibility and compatibility of the strontium ferrite, so that the strontium ferrite is more evenly distributed in the concrete, forming a more stable structure, further improving the antistatic and radiation protection properties of the concrete, and avoiding the agglomeration of the strontium ferrite due to its own magnetism, thereby affecting the overall radiation protection performance;
[0113] It can be seen from Examples 13-14, 12 and Table 3 that the concrete prepared in the present application using steel slag, river sand and crushed stone of specific particle sizes has excellent comprehensive performance.
[0114] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, all equivalent changes made according to the principles of the present application should be included in the protection scope of the present application.
Claims
1. An anti-static and anti-radiation concrete, characterized in that: The raw materials include the following parts by weight: 250-380 parts of cement, 70-200 parts of steel slag, 500-750 parts of river sand, 600-800 parts of crushed stone, 125-190 parts of water and 35-65 parts of additives; Wherein, the additives are strontium ferrite and hafnium boride; the weight ratio of the strontium ferrite to the hafnium boride is 1-1.5:
1.
2. The anti-static and radiation-proof concrete according to claim 1, characterized in that: The weight proportion of the additive is 42-55 parts.
3. The anti-static and radiation-proof concrete according to claim 1, characterized in that: The ratio of the weight of the additive to the sum of the weight of the cement and the steel slag is 0.07-0.144:
1.
4. The anti-static and radiation-proof concrete according to claim 1, characterized in that: The strontium ferrite is replaced by modified strontium ferrite, wherein the raw materials of the modified strontium ferrite include a surface treatment agent, a polyurethane emulsion and strontium ferrite, and the weight ratio of the surface treatment agent, the polyurethane emulsion and the strontium ferrite is 4:100:
30.
5. The anti-static and radiation-proof concrete according to claim 4, characterized in that: The surface treatment agent is obtained by mixing sodium hexametaphosphate, sodium lauryl sulfate and ethanol solution in a weight ratio of 3:1:
100.
6. The anti-static and radiation-proof concrete according to any one of claims 1 to 5, characterized in that: The average particle size of the steel slag is 1-5 mm.
7. The anti-static and radiation-proof concrete according to any one of claims 1 to 5, characterized in that: The fineness modulus of the river sand is 2.3-2.
9.
8. The anti-static and radiation-proof concrete according to any one of claims 1 to 5, characterized in that: The average particle size of the crushed stone is 6-15 mm.
